PERLINDUNGAN HUKUM BAGI PELAKU USAHA KERAJINAN TANGAN ATAS KONSUMEN YANG MELAKUKAN PEMBATALAN SEPIHAK DI KOTA BALIKPAPAN - Orly Octavia Nureni; Irma Suriyani; Safarni Husain (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2024)
Business actors are important subject in sale and purchase. However, there is a problem where consumers make unilateral cancellation and cause harm to business actors. This research is conducted with the aim to identify the form of legal protection for business actors and to examine the agreement in order to minimize the risk due to unilateral cancellation in handicraft business actors in Balikpapan City. The result of the research shows that legal protection for business actors is based on the implementation of good faith, rights and obligatins of each party which are regulated in KUHPer and UUPK. However, the function of the agreement to minimize the risk due to unilateral cancellation can be maximized through using a specific and complete agreement, which includes importat matters in the sale and purchase, such as down-payment provisions, cancellation provisions, and other provisions, in order to ensure legal certainty and protection for the parties.